Increased antidepressant prescriptions following the 2018 Japan floods: a longitudinal analysis using the national health insurance database - Miyuki Hattori; Shuhei Yoshida; Shinichiro Ohshimo; Nobuaki Shime; Masatoshi Matsumoto (European Journal of Psychotraumatology)
Background: Natural disasters are known to affect the mental health of the victims; however, the understanding of their impact on real-world clinical practice remains insufficient.Objective: This study aimed to evaluate the effects of the 2018 Japan floods, one of the largest disasters in Japan’s recorded history, on antidepressant prescriptions over time.Method: Prescription data from the medical insurance claims database covering three prefectures that accounted for 90% of flood damage were analyzed for the years before and after the floods. Participants were categorized as disaster victims or nonvictims based on local government designations. A difference-in-differences analysis compared the trends in antidepressant prescriptions between victims and non-victims during the period surrounding the floods.Results: Of 5,000,129 participants, 31,235 were disaster victims. Victims were more likely to be prescribed antidepressants after the disaster than nonvictims (p < .001). This trend peaked 2–3 months after the disaster (adjusted Ratio of Odds Ratios [ROR], 1.13; 95% confidence interval [CI] 1.07–1.20) and persisted up to 1 year later (adjusted ROR, 1.20; 95% CI 1.12–1.28). Among antidepressants, noradrenergic and specific serotonergic antidepressants (NaSSAs) and serotonin antagonist and reuptake inhibitors (adjusted ROR 1.47, 1.49; 95% CI 1.21–1.80, 1.22–1.83) were particularly prescribed more frequently among victims. When limited to those who had not used antidepressants before the disaster, NaSSAs (adjusted ROR 2.56; 95% CI 2.14–3.07, p < .001) were conspicuously more prescribed.Conclusions: The floods were associated with an increase in antidepressant prescriptions, suggesting the development of disaster-related mental health conditions such as depression and post-traumatic stress disorder. The need for care became pronounced 2–3 months after the event and persisted for 1 year. These findings highlight the need for psychiatric drug treatment among disaster victims and emphasize the importance of identifying appropriate timing for such interventions.